Simulations of the time and space-resolved X-ray transmission of a free-electron-laser-heated aluminium plasma - Rackstraw, D; Vinko, S; Ciricosta, O; Chung, H; Lee, R; Wark, J (IOP Publishing, 2016)
We present simulations of the time and space-resolved transmission of a solid-density aluminium plasma as it is created and probed with the focussed output of an x-ray free-electron-laser with photon energies ranging from the K-edge of the cold material (1560 eV) to 1880 eV. We demonstrate how information about the temporal evolution of the charge states within the system can be extracted from the spatially resolved, yet time-integrated transmission images. We propose that such time-resolved measurements could in principle be performed with recently developed split-and-delay techniques.